A Current Review of Literature on Cardiovascular Diseases in Schizophrenic Patients - Mohammed Tahayneh; Rami Jamil Jaber; Barani Karikalan; Mohamed Gwila; Syeda Humayra (Asian Journal of Medicine & Health Sciences, 2023)
Globally, cardiovascular disease (CVD) persists as a major contributor to death. CVD has been strongly associated to psychological factors, and the link appears to be bidirectional. This is because certain psychological conditions may pre-exist and precede CV diseases and lead to worse clinical outcomes. Generally, mortality from CVD prevails to be higher in individuals with mental health problems, particularly schizophrenia. In order to understand the impact of CVDs among schizophrenic individuals, targeted efforts at the clinic, community, and policy levels are highly required. Knowledge gaps have been previously identified in regard to the prevalence of CVDs among schizophrenic patients. Keeping in mind, the complexity of both the diseases and their coexistence, this paper aims to review the current state of literature regarding cardiovascular diseases among schizophrenic patients, and highlight the importance of patient-centred care, risk factors, management strategies and interventions.